2014
DOI: 10.1007/s12032-014-0407-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of apolipoprotein A-I kinetics with survival and response to first-line platinum-based chemotherapy in advanced non-small cell lung cancer

Abstract: The aim of this study was to determine whether apolipoprotein A-I (ApoA-I) kinetics predict the overall survival in patients with advanced-stage non-small cell lung cancer (NSCLC) during platinum-based first-line therapy. A total of 125 NSCLC patients from January 2008 to September 2014 were retrospectively reviewed. Serum ApoA-I level was measured at baseline and thereafter at the start of each palliative chemotherapy cycle for all patients. Patients were divided into four groups according to ApoA-I kinetics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Patients with advanced stage non-small cell lung cancer and persistently high serum apoA-I levels had the highest overall median survival at 36 months, whereas patients with persistently low serum apoA-I levels had the lowest median overall survival. This suggests that higher serum apoA-I levels were associated with a lower rate of disease progression in non-small cell lung cancer (91). In contrast, serum levels of pro-apoA-I have been found to be specifically and selectively increased only in patients with lung cancer that had metastasized to the brain (92).…”
Section: Apoa-i and Lung Cancermentioning
confidence: 99%
“…Patients with advanced stage non-small cell lung cancer and persistently high serum apoA-I levels had the highest overall median survival at 36 months, whereas patients with persistently low serum apoA-I levels had the lowest median overall survival. This suggests that higher serum apoA-I levels were associated with a lower rate of disease progression in non-small cell lung cancer (91). In contrast, serum levels of pro-apoA-I have been found to be specifically and selectively increased only in patients with lung cancer that had metastasized to the brain (92).…”
Section: Apoa-i and Lung Cancermentioning
confidence: 99%
“…The level of ApoA-I for prognosis in a range of malignancies has been previously investigated and has demonstrated an inverse relationship between the ApoA-I level and the length of survival time in ovarian cancer, lung cancer, and metastatic nasopharyngeal carcinoma [8], [9], [10]. To the best of our knowledge, this retrospective study is the first to describe the impact of the ApoA-I level on the survival of patients with mCRC.…”
Section: Discussionmentioning
confidence: 83%
“…ApoA-I has been identified as a potentially useful biomarker for effectively distinguishing cholangiocarcinoma from benign biliary disease and improving the early diagnosis of ovarian cancer [7], [8]. Moreover, decreased serum ApoA-I has been shown to be correlated with worse overall survival in lung cancer and metastatic nasopharyngeal carcinoma [9], [10]. The role of ApoA-I in patients with mCRC has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study reported that low serum ApoA-I levels were associated with advanced T class and TNM stage and systemic inflammation biomarkers in CRC. All of these findings indicate that serum ApoA-I may participate in multiple processes in the occurrence and development of cancers [19,20,[29][30][31].…”
Section: Discussionmentioning
confidence: 89%